Zakat Sebagai Pengurang (Penghasil Kena) Pajak - hasan, dahlawi; slamet, Slamet; laili, afrohatul (LPPM UNU BLITAR, 2024)
In accordance with Islamic sharia, zakat is imposed on two things, namely on every living human soul (an-nafs) and on assets (maal) that meet the requirements. Zakat on the soul is called zakat fitrah, it is paid once a year in the holy month of Ramadan before the Eid al-Fitr prayer, it is paid in the form of one sha' of staple foods such as rice, wheat, corn or according to some scholars zakat fitrah can be paid in the form of money equivalent to the price of one sha' of these staple foodstuffs. Management under the authority of an agency established by the State will be much more effective in carrying out its functions and impact in building the welfare of the people who are the goal of zakat itself, compared to zakat being collected and distributed by institutions that run independently and have no coordination with each other. To facilitate the obligation to pay zakat for Muslims in Indonesia, the law stipulates the government's obligation, namely to provide protection, guidance and services to muzakki, mustahiq and amil zakat.